Utilisation of food wastes for the production of organic acids and bioplastics - Abdul Wahab, Norrizan (2003)
In this study, food wastes were used as substrates for the production of polyhydraxyalkanoate (PHA) by Ralstonia eutropha (formerly known as Alcaligenes eutrophus). Restaurant waste obtained from a local restaurant and house was blended with an equal weight of water. PHA production was achieved via a two-stage process; organic acids production from food waste followed by PHA production from the organic acids. In the first stage. the study focused on the production of short-chain organic acids from complex organic fraction of food waste. The food waste was subjected to anaerobic treatment by the natural micro flora present in a 2-liter batch stirred tank bioreactor with mixing at 200 - 400 rpm. The effect of pH, temperature, substrate compositions of food waste on the production of volatile fatty acids (VFA) was evaluated. For the effect of different pH, the batch anaerobic medium was done [uncontrolled pH, controlled at pH 7 for different number of days (initial, one day, two days and whole duration)].The effect of different temperatures (30°C, 37°C, 45°C) and different substrate compositions [kitchen waste (A), restaurant waste (B) and restaurant waste mixed with fruits waste (C)] have been done in the research. Restaurant waste mixed with fruit waste (substrate C) produced 58 g/L organic acids compared to 42 g/L from kitchen waste (substrate A) under same conditions at 37°C without control pH. Lactic acid was the most predominant acid. followed by acetic, propionic, butyric and formic acids. The study on the effect of temperature with uncontrolled pH shows that 37°C is the best temperature, producing 58 g/L organic acids. with 83% lactic acid. In the effect of pH. it was found that the highest amount of organic acids produced was 68 g/L with 84% lactic acid when the initial pH was adjusted to 7.0 without further pH control. Overall the best conditions for organic acids production is pH controlled at 7 in the initial treatment at 37°C using restaurant wastes containing fruit waste. Studies on microbial and enzyme activity was done on treated food waste to determine the factors contributing to the high organic acids especially lactic acid. From the microbes identified. Lactobacillus was predominantly involved in the fermentation to produce lactic acid. The enzyme lipase, protease. cellulase and a-amylase were detected throughout the treatments leading to the conversion of organic complex to sugar and subsequently to organic acids with a-amylase as the highest activity. In the recovery of organic acids from the fermented food waste, centrifugation was carried out to remove the solids and oils. The supernatant was collected and concentrated by evaporation for the second stage of bioplastic production.The results show that by evaporation method, the organic acids were concentrated two-fold to about 100 g/L for use as substrates for fed:-batch fermentation. PHA production from organic acids fermented from food waste, as a carbon source for fedbatch fermentation is 4.2 g/L with 88% of dry cell weight. From the experiment, CIN 10-20 because ammonium concentration in the original food waste was high. This encouraged cell growth in the medium rather than PHA production. In the PHA production, since CIN must be high (around 100-150). removal of ammonium was successfully achieved using Dowex 88wx resin for improved PHA production. The ammonia-deficient organic acids from food wastes were successfully converted to PHA by Ralstonia eutropha strain ATCC 17699. producing 8.9 giL with 90%(g/g) PHA content.